Sequential formation of two branched intermediates during protein splicing of class three inteins - Tori, Kazuo (Extremophiles, 2016)
Inteins are the protein equivalent of introns. They are seamlessly removed during post-translational maturation of their host protein (extein). Inteins from extremophiles played a key role in understanding intein-mediated protein splicing. There are currently three classes of inteins defined by catalytic mechanism and sequence signatures. This study demonstrates splicing of three class 3 mini-inteins: Burkholderia vietnamiensis G4 Bvi IcmO intein, Mycobacterium smegmatis MC2 155 Msm DnaB-1 intein and Mycobacterium leprae strain TN Mle DnaB intein. B. vietnamiensis has a broad ecological range and remediates trichloroethene. M. smegmatis is a biofilm forming soil bacteria. Although other intein classes have only a single branched intermediate at the C-terminal splice junction, the class 3 intein reaction pathway includes two branched intermediates. The class 3 specific branched intermediate is formed by an internal cysteine, while the C-terminal branch intermediate is at a serine or threonine in all class 3 inteins except the Bvi IcmO intein, where it is a cysteine. This latter cysteine was unable to compensate for mutation of the class 3-specific internal catalytic cysteine despite the Bvi IcmO intein having an N-terminal splice junction naturally tuned for a cysteine nucleophile, demonstrating the mandatory order of branch intermediates in class 3 inteins.